A narrative review focusing on randomized clinical trials of vitamin D supplementation for COVID-19 disease - Huang, Limi; Song, Zhiwei; Lu, Chaosheng; Wang, Shenwen; Guo, Changsheng; Lai, Xin-He; Zhao, Zhenfeng (Frontiers in Nutrition, 2025)
Current evidence is inconsistent on whether vitamin D supplementation can prevent COVID-19 infection or improve its clinical outcomes. To better understand and look into the issue, we went through the background knowledge of COVID-19 and vitamin D, searched in Pubmed [by using key words in the title containing 'randomized clinical trial ', or cholecalciferol, or calcidiol, or calcifediol) supplementation'] for publications of studies on vitamin D/supplementation in COVID-19 patients, especially those about the randomized clinical trials (RCTs). After reviewing these papers, we did a short background review of vitamin D and the pathophysiology of COVID-19, summarized the key features of the 25 RCTs in text and tabulated in a table of some of the features, commented, compared and discussed the differences between RCTs (for example, change the serum 25-hydroxyvitamin D concentration from nmol/L to ng/mL, making the comparison easier). The take-home question of the review is that serum 25-hydroxyvitamin D concentration is an important indicator of the supplementation effect of vitamin D correction but may not be reliable in predicting the supplementation effect on the clinical outcomes of COVID-19.